Ex Vivo Biomechanical Assessment of Various Repair Techniques in a Rabbit Calcaneal Tendon Avulsion Model: Application of Polycaprolactone Plate - Zheng Huidan; Jinsu Kang; Namsoo Kim; Suyoung Heo (Veterinary Sciences, 2023)
This study was aimed at evaluating the biomechanical properties and gapping characteristics of tendon repair methods using a combination of a three-loop pulley (3LP) pattern, a titanium plate, and a polycaprolactone (PCL) plate in a rabbit gastrocnemius tendon (GT) model (n = 50). GTs were randomly assigned to five groups (n = 10/group). Transected GTs were repaired with a 3LP pattern alone or in conjunction with an epitendinous suture (ES), a 5-hole 1 mm PCL plate, a 5-hole 2 mm PCL plate, or a 5-hole 1.5 mm titanium plate. The yield, peak, and failure force, as well as the occurrence and force of 1-mm and 3-mm gapping were examined. The mean yield, peak, and failure force of the 3LP + titanium plate group were higher than that of other groups. The biomechanical properties of a 3LP + a 2 mm PCL plate were similar to 3LP + ES constructs in this model. In all specimens in all groups, 1 mm gap formation was observed. The frequency of 3 mm gap formation was 70% and 90% in the 3LP + 2 mm PCL plate group and the 3LP + 1.5 mm titanium plate group, respectively. Additional studies evaluating PCL plates to determine the effect on the healing and blood supply of tendon are needed.